Teknik Psikodrama dalam Mengembangkan Kontrol Diri Siswa - Sari, Syska Purnama (Jurnal Dosen Universitas PGRI Palembang)
Abstract: This research is motivated by the phenomenon of juvenile delinquency. Teenagers often do not have good self-control. If self-control skills are developed early on, adolescents are expected to be able to control themselves from deviant behavior that can damage theirlives in the future. The purpose of this research is to know the general description of self- control of fourth-grade students of SD Negeri 1 Lubuk Ngin and to test the effectiveness of psychodrama in developing student self-control. The research is done using quasi- experimental method. The research subject is the fourth grader of SD Negeri 1 Lubuk Ngin. The results showed that Psikodrama technique is effective in developing self-control fourth- grade students SD Negeri 1 Lubuk Ngin.Keywords: Self Control, Psychodrama